HarmoSim: A tool for harmonic distortion simulation and assessment of nonlinear loads. Issue 2 (14th June 2011) - Baptista, J.; Morais, R.; Valente, A.; Soares, S.; Candeias, M.; Reis, M.J.C.S.
ABSTRACT Electrical power quality (PQ) is a crucial competitive and developing factor to all economic activities. The economic impact resulting from a bad PQ would be drastic on all consumers. Computers, uninterruptible and switched power supplies (UPS), and fluorescent lamps/tubes are examples of nonlinear loads that have the consumption of a nonsinusoidal current, which cause disturbances in the power supply system (that may be severe or not). This study discusses residential generic power circuitry analysis and simulation, under nonlinear loads, in connection with undergraduate electrical engineering education. It briefly reviews some of the basic techniques, and presents a software tool that has been found to be very useful in the context. The tool has an easy‐to‐use, friendly interface, and can be used to teach design techniques or as a laboratory support to study the applicability of known methods to real situations. The students can perform simulations with their own data on Microsoft™ Windows®‐based platforms. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:340–348, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.20559